Models of speed development in soccer - Krosta, R.; Drozd, M.; Góralczyk, R.; Kostrzewa, M.; Fischerova, P.; Ignatieva, A. (Baltic Journal of Health and Physical Activity, 2020)
Background: The main objective of this research was to determine a model of the Speed Abilities Development Index (SADI) in selected teams of the top league, the first and the second league in Poland. The indirect aim was to determine the most significant predictors that have the greatest effect on development of this model.